An Archetypal Journey: Hero’s Transformation in Hetchchhakuppa, a Kirant Mythic Play - Rai, Prakash (Literary Studies, 2024)
The paper examines the archetypal journey of Hetchhakuppa in the Kirant mythic play, Hetchchhakuppa written and directed by Prabin Puma to spot his metamorphosis from an innocent to an experienced individual, from a physical being to a spiritual and from a paleolithic to a neolithic existence. Employing Joseph Campbell's idea of the hero's journey passing through several stages for transformations, the study delves into the heroic journey of the hero, Hetchchhakuppa, which embodies the universal journey of human beings for the advancement of humanism and the world. The notion of “transformations of the hero through the journey” by Campbell to trace the hero's multiple levels of transformations and Jung's "archetype symbolism' to explore a deeper level of the hero's psychical transformation through different stages of the journey serve as a foundation for analyzing and interpreting the texts of the play. The archetypal hero, Hetchchhakuppa's incessant adventure brings transformative changes in his individual and collective life developing self-realization, growth, maturity, and resurrection out of the exotic expeditions. His transformative journey exhorted by dynamic movement and commitment despite the hardship and adversity invigorates him to transcend the constraints of physical boundaries, self-absorption, and naivety for triumphing over stagnant nature. The journey Hetchchhakuppa takes on mirrors a common journey of all mankind to sustain humanity and his steadfast commitment to perpetuating the expedition reflects a shared yearning for progress and transformation not only of the individual but also of the universal man.